Análise dos fatores de risco e do índice de exposição a LER/DORT dos trabalhadores em atividades repetitivas: estudo de caso - Leite, Sheysa Danyelle de Freitas (2013)
The objective of this study is to analyze the influence of risk factors on exposure to WMSD workers in repetitive activities in the footwear sector. Therefore, we analyzed the data for 71 workplaces in the productive area of a shoe company which are characterized by having a defined task cycle, and had the index of exposure to WMSD upper limbs calculated through the OCRA method. Data analysis was accomplished using the exploratory data analysis of WMSD and construction of a Generalized Linear Model (GLM). This model identified the factors that influence the rate of exposure the most and made it possible to quantify the possible chance of raising this index when risk factors are present in the workplaces. The factor indicated as the most influential one was the "sudden movements" factor, the presence of this factor increases the chance of raising the level of exposure in 2.12 times more than when this factor is not present.